PERSPEKTIF MASLAHAH TERHADAP PERTIMBANGAN HAKIM PADA PUTUSAN PERKARA NOMOR: 1376/Pdt.G/2019/PA.Tnk TENTANG PENETAPAN HAK HADANAH KEPADA IBU KANDUNG - Jayusman, Jayusman; Huda, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2021)
The protection of women and children is one of problems in the Indonesian judiciary. In the decision on Case Number: 1234/Pdt.G/2018/PA.Tnk and Number: 0014/Pdt.G/2019/PTA. Bdl which has permanent legal force regarding child custody by the Plaintiff. However, the Defendant was reluctant and did not want to implement the decision. So the Plaintiff must file a new lawsuit for the execution of the previous decision with decision number: 1376/Pdt.G/2019/PA.Tnk. The problem with this article is based on the judge's consideration of decision number: 1376/Pdt.G/2019/PA.Tnk regarding the determination of child custody to his biological mother. This research is library which is descriptive analytical. The primary data is in the form of decision number: 1376/Pdt.G/2019/PA.Tnk and is complemented by secondary data. Data were collected through documentation techniques and the analysis was carried out since the data collection process and deductively. The results of this study indicate that the judge's consideration in the case decision Number: 1376/Pdt.G/2019/PA.Tnk regarding the determination of child custody to the biological mother is based on the benefit and goodness of the child. The declarative nature of the previous decision prevented the realization of benefit values for the parties. The reason usually regarding child custody are executed voluntarily and not by force. The plaintiff seeks to obtain the power of legal execution from the previous decision by filing a new lawsuit with a comdennatoir decision, so that the child can be handed over to him to be treated as well as possible.